การดำรงอยู่ของผู้ผลิตยางพารารายย่อยในหมู่บ้านห้วยพลูหนัง จังหวัดกระบี่ - พรศิริ เจริญสืบสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research analyzes the existence of the small rubber farmers in Ban Huayplu Nang, a village of Krabi province under the influence of capitalism. The framework in use is that of the Marxist Political Economy for which it provides this study as a guideline. The information showing in the research were collected by interviewing small rubber farmers, workers and people who were relevant to the processes of rubber production. The study finds that the small rubber farmers, as the majority of the village, are in disadvantageous positions to the local capitalists as merely its counter parts, i.e., labourers. The main reason-cum-empirical evidences shows that the small rubber farmers were subsumed or integrated into the capitalist circuits via its process of production through the uses of new technologies. The state, as a mediator, were not capable of improving the "labour" conditions of the small farmers simply due to its sharing benefits with the local capitalist.